Progressive multiple sclerosis: prospects for disease therapy, repair, and restoration of function. Issue 10076 (1st April 2017) - Ontaneda, Daniel; Thompson, Alan J; Fox, Robert J; Cohen, Jeffrey A
Summary: Multiple sclerosis is a major cause of neurological disability, which accrues predominantly during progressive forms of the disease. Although development of multifocal inflammatory lesions is the underlying pathological process in relapsing-remitting multiple sclerosis, the gradual accumulation of disability that characterises progressive multiple sclerosis seems to result more from diffuse immune mechanisms and neurodegeneration. As a result, the 14 anti-inflammatory drugs that have regulatory approval for treatment of relapsing-remitting multiple sclerosis have little or no efficacy in progressive multiple sclerosis without inflammatory lesion activity. Effective therapies for progressive multiple sclerosis that prevent worsening, reverse damage, and restore function are a major unmet need. In this Series paper we summarise the current status of therapy for progressive multiple sclerosis and outline prospects for the future.